Cardiac Resynchronization Therapy in a Chagasic Patient With Persistent Left Superior Vena Cava - Lucas Hollanda, MD, MSc; Ricardo Sobral, MD; Christian Luize, MD; William Carvalho, RN; Marcel Carvalho, MD; Luiz Passos, MD, PhD (JACC: Case Reports, 2019)
This report describes the case of a woman with Chagas' cardiomyopathy with severe left ventricular dysfunction and persistent left superior vena cava who presented with episodes of syncope without prodromes and who was referred for cardiac resynchronization therapy. Despite this venous anomaly, electrodes were safely positioned in suitable locations. (Level of Difficulty: Intermediate.)